First-year growth of 834 preterm infants in a Chinese population: a single-center study - Ying Deng; Fan Yang; Dezhi Mu (BMC, 2019)
Abstract Background The aim of this study was to follow the growth and hematological indicators of preterm infants during their first year. Methods Neonates below 37 gestational weeks had routine follow-ups up through 1 year from January 2012 to December 2015 at West China 2nd University Hospital, Sichuan University. Weight, length and head circumference (HC) were measured monthly during the first 6 months, followed by monitoring every second month until 12 months. The catch-up growth defined as a gain of Z-score > 0.67 according to previous study. All preterm infants were prescribed iron prophylaxis based on national guideline. The hemoglobin concentration was examined at 6 and 12 months. Results Altogether, 132 very-low-birth-weight (VLBW), 504 low-birth-weight (LBW) and 198 normal-birth-weight (NBW) infants were followed. The rates of catch-up growth for weight, length and HC 12 months of corrected age (CA) were 22.6, 29.1 and 14.6%, respectively. SGA and VLBW infants showed higher catch-up growth rates. The overall prevalence of anemia was 6.8% at 6 months and 7.8% at 12 months. The Z-scores for weight-for-length, length and HC were lower in the VLBW and SGA preterm infant groups than in the other preterm groups throughout the first year of life. The incidences of stunting, microcephaly and wasting changed from 5, 1.3 and 3.7% to 2, 1.1, 0.9 and 2.4%, respectively, during the first year. However, the incidences of wasting and stunting were higher for the VLBW infants than for the LBW and NBW infants at 12 months (9.3% vs. 1.4%, p < 0.01; 9.3% vs. 1%, p < 0.01,respectively; 4.7% vs. 0.8%, p < 0.01, 4.7% vs. 0%, p < 0.01,respectively). Similar results were observed between SGA and AGA infants (8.7% vs. 1.5%, p < 0.01; 5.8% vs. 0.4%, p < 0.01). Logistic regression revealed SGA and VLBW as risk factors for poor growth (WLZ < -2SD) at 12 months (OR = 5.5, 95% CI: 2.1-14.8, p < 0.01: OR = 4.8, 95% CI: 1.8-12.8, p < 0.01, respectively). Conclusion The VLBW and SGA preterm infants showed significant catch-up growth during their first year of life. However, SGA and VLBW were risk factors for poor growth during the preterm infants' first year of life. Prophylactic iron supplementation in preterm infants appears to reduce the prevalence of anemia.